Editorial - Revista Educação - Cláudia Ribeiro Belochio; Doris Pires Vargas Bolzan; Silvia Maria de Aguiar Isaia; Adriana Moreira da Rocha Maciel (Universidade Federal de Santa Maria, 2011)
- Revista Educação